Inhibition of maternal embryonic leucine zipper kinase with OTSSP167 displays potent anti-leukemic effects in chronic lymphocytic leukemia. Issue 41 (11th October 2018) - Zhang, Ya; Zhou, Xiangxiang; Li, Ying; Xu, Yangyang; Lu, Kang; Li, Peipei; Wang, Xin
Abstract TP53 pathway defects contributed to therapy resistance and adverse clinical outcome in chronic lymphocytic leukemia (CLL), which represents an unmet clinical need with few therapeutic options. Maternal embryonic leucine zipper kinase (MELK) is a novel oncogene, which plays crucial roles in mitotic progression and stem cell maintenance. OTSSP167, an orally administrated inhibitor targeting MELK, is currently in a phase I/II clinical trial in patients with advanced breast cancer and acute myeloid leukemia. Yet, no investigation has been elucidated to date regarding the oncogenic role of MELK and effects of OTSSP167 in chronic lymphocytic leukemia (CLL). Previous studies confirmed MELK inhibition abrogated cancer cell survival via p53 signaling pathway. Thus, we aimed to determine the biological function of MELK and therapeutic potential of OTSSP167 in CLL. Herein, MELK over-expression was observed in CLL cells, and correlated with higher WBC count, advanced stage, elevated LDH, increased β2-MG level, unmutated IGHV, positive ZAP-70, deletion of 17p13 and inferior prognosis of CLL patients. In accordance with functional enrichment analyses in gene expression profiling, CLL cells with depletion or inhibition of MELK exhibited impaired cell proliferation, enhanced fast-onset apoptosis, induced G2/M arrest, attenuated cell chemotaxis and promoted sensitivity to fludarabine and ibrutinib. However, gain-of-function assay showed increased cell proliferation and cell chemotaxis. In addition, OTSSP167 treatment reduced phosphorylation of AKT and ERK1/2. It decreased FoxM1 phosphorylation, expression of FoxM1, cyclin B1 and CDK1, while up-regulating p53 and p21 expression. Taken together, MELK served as a candidate of therapeutic target in CLL. OTSSP167 exhibits potent anti-tumor activities in CLL cells, highlighting a novel molecule-based strategy for leukemic interventions.